2013
DOI: 10.1371/journal.pone.0082449
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-Like Factor 6 Rendered Rat Schwann Cell More Sensitive to Apoptosis via Upregulating FAS Expression

Abstract: Krüppel-like factor 6 (KLF6) is a tumor suppressor gene and play a role in the regulation of cell proliferation and apoptosis. After the peripheral nerve injury (PNI), the microenvironment created by surrounding Schwann cells (SCs) is a critical determinant of its regenerative potential. In this study, we examined the effects of KLF6 on SCs responses during PNI. Both KLF6 mRNA and protein expression levels were upregulated in the injured sciatic nerve, and immunofluorescence results showed that many KLF6-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Real-time PCR were processed according to our previous protocols [ 19 ]. Briefly, astrocytes were incubated in serum-free DMEM containing 0, 5 or 20 μM MK-801 for 24 h and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR were processed according to our previous protocols [ 19 ]. Briefly, astrocytes were incubated in serum-free DMEM containing 0, 5 or 20 μM MK-801 for 24 h and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the antiapoptosis protein Bcl2 was upregulated in NRBP2 low cells, whereas the proapoptosis protein Bax was downregulated. Bax/ Bcl2 ratio could reflect the propensity or resistance to apoptosis (25). Then, Bax/Bcl2 ratio was calculated and the results displayed that the Bax/Bcl2 ratio was decreased in the NRBP2 low cells (Fig.…”
Section: Nrbp2 Inhibits Akt Phosphorylation and Regulates Bcl2 Familymentioning
confidence: 97%
“…The results are responsible for three independent experiments Cell Mol Neurobiol In higher vertebrates, the capacity of the PNS to regenerate is robust compared to that of the CNS. The regeneration potential of peripheral nerve may due to the proliferation and activation of Schwann cells, which produce growth factors that promote axonal regrowth at the proximal nerve stump and provide a growth-permissive condition for axon guidance (Gui et al 2013;Hall 2001). Although the role of PCBP2 in the PNS has not been reported before our research, many studies focused on the function of PCBP2 gene in the CNS and many other diseases.…”
Section: Discussionmentioning
confidence: 78%